In Vitro Selection of Neisseria gonorrhoeae Mutants with Elevated MIC Values and Increased Resistance to Cephalosporins - Johnson, Steven R. (Antimicrob Agents Chemother, 2014)
Strains of Neisseria gonorrhoeae with mosaic penA genes bearing novel point mutations in penA have been isolated from ceftriaxone treatment failures. Such isolates exhibit significantly higher MIC values to third-generation cephalosporins. Here we report the in vitro isolation of two mutants with elevated MICs to cephalosporins. The first possesses a point mutation in the transpeptidase region of the mosaic penA gene, and the second contains an insertion mutation in pilQ.